2019
DOI: 10.1038/s41598-019-48502-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of TIMOLOL nasal spray as a treatment for epistaxis in hereditary hemorrhagic telangiectasia. A double-blind, randomized, placebo-controlled trial

Abstract: Hereditary hemorrhagic telangiectasia is a rare vascular genetic disease. Epistaxis is the most frequent and disabling manifestation, and timolol appears to be a new therapeutic option as non-selective beta-blockers have in vitro and in vivo anti-angiogenic properties. Our main objective was to evaluate the efficacy of TIMOLOL nasal spray as a treatment for epistaxis in hereditary hemorrhagic telangiectasia. This study is a single-center, randomized, phase 2, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
0
19
0
2
Order By: Relevance
“… 32 Topical nasal pharmacotherapy has been similarly disappointing, with randomized studies of topical timolol, estrogen, and tranexamic acid all showing no difference in the comparison with placebo. 33 , 34 Bevacizumab via topical nasal spray has also been evaluated, with no improvement noted in epistaxis severity in the comparison with placebo. 33 , 35 Therefore, given the lack of other effective options and the continued lack of any Food and Drug Administration-approved treatment, our findings suggest it may be appropriate to consider systemic bevacizumab in patients with moderate-to-severe HHT-associated bleeding ( Online Supplementary Table S1 ) without contraindications.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Topical nasal pharmacotherapy has been similarly disappointing, with randomized studies of topical timolol, estrogen, and tranexamic acid all showing no difference in the comparison with placebo. 33 , 34 Bevacizumab via topical nasal spray has also been evaluated, with no improvement noted in epistaxis severity in the comparison with placebo. 33 , 35 Therefore, given the lack of other effective options and the continued lack of any Food and Drug Administration-approved treatment, our findings suggest it may be appropriate to consider systemic bevacizumab in patients with moderate-to-severe HHT-associated bleeding ( Online Supplementary Table S1 ) without contraindications.…”
Section: Discussionmentioning
confidence: 99%
“…The studies cited have also noted no adverse effects following the initiation of beta blockers when contraindications are considered. 8,9,13 The observed improvement of ESS for these patients is likely multifactorial. Whilst it is possible that topical +/À systemic beta blocker could improve symptoms, the prolonged and accessible support from the multidisciplinary team and simple regimented application of nasal emollients could also contribute to the improvement of ESS.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, blood pressure lowering medication may be beneficial. Propranolol, a nonselective β-blocker with antiangiogenic effects, has shown some benefit used topically on nasal telangiectases [73], although a double blind randomized placebo-controlled trial using topical application of the β-blocker Timolol showed no benefit on epistaxis [53].…”
Section: β-Blockersmentioning
confidence: 99%